Methods and products for producing metal oxide pigment composites with controlled aggregation properties
Patent Information
- Application Number
- JP2022519377
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-27
- Filing Date
- 2020-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-09-23
AI Technical Summary
Commercially available pigments with particle sizes closer to the micrometer scale face challenges in achieving uniform dispersion and distribution due to sedimentation, creaming, flocculation, and coalescence, leading to instability and undesirable properties in formulations, particularly in cosmetic and coating applications.
A process involving ball milling of metal oxide pigments with oligomeric and/or polymeric carbohydrates to produce submicron-sized pigment composites, where the pigments are coated with these organic compounds to stabilize them against aggregation, ensuring stable dispersion and improved formulation properties.
The process results in pigment composites with reduced particle sizes and enhanced stability, allowing for uniform dispersion in aqueous media, maintaining color intensity and preventing adherence to packaging materials, with improved shelf life and formulation stability.
Smart Images

Figure 00000023_0000 
Figure 00000023_0001 
Figure 00000023_0002
Abstract
Description
Technical Field
[0001] The present invention relates to pigments and formulations of cosmetics and coatings containing them, particularly to aqueous-based pigment compositions with a submicron particle size distribution and their dispersions.
Background Art
[0002] In several industrial applications, particularly in the field of cosmetics, pigments generally need to have a size between 0.3 μm and 0.8 μm.
[0003] Commercially available pigments have particle sizes closer to the micrometer scale rather than the nanometer scale, making it difficult to obtain a uniform dispersion, and thus it has become difficult to ensure a uniform coating of the surface to which the pigmented formulation is applied.
[0004] The particle size of commercially available pigments can even range from 0.1 μm to 10 μm.
[0005] During storage life, various grinding techniques can be used to produce formulations that are homogeneous and probably uniformly coat various types of surfaces.
[0006] The stability of the formulation in which the pigment is dispersed is improved by reducing the particle size to the submicron scale, and the overall quality during the application of such a formulation is also improved. For example, the unwanted stripe formation phenomenon is reduced.
[0007] Size reduction by milling is well-known and is a simply designed method that is applicable not only to the production of metals but also as a post-treatment for the production of various solids.
[0008] By changing the milling parameters, the particle size that is reduced during the milling process can be controlled.
[0009] However, when pigment particles are dispersed in a particular suspension or formulation, they tend to fuse together during contact to form larger particles, and separation of the suspension and formulation is determined by phenomena such as sedimentation, creaming, coagulation, and / or coalescence.
[0010] Specifically, while the most commonly used metal oxide-based pigments induce the formation of stable compositions in neutral to weakly basic environments, the colloidal properties of the derived microstructures and nanostructures exhibit considerable instability with increasing pH of the dispersion medium. The acceleration of pH-dependent aggregation and destabilization of iron oxide nanoparticles is disclosed in Non-Patent Literature 1.
[0011] Wetting and dispersion additives are used to improve physicochemical and colloidal properties.
[0012] The use of artificial surfactants as wetting and dispersion additives is known in the art.
[0013] Surfactants can interact in various ways, but non-bonding interactions are usually dominant among them. Among these interacting forces, electrostatic properties have traditionally been considered the most important stabilizing factor. In water-based dispersions, concentrated pigment particles are surrounded by an electrochemical bilayer of oppositely charged ions or dipoles that are closely attached to the pigment.
[0014] The strength of attractive and repulsive forces depends on distance, and in strong and distinct bilayers, the coefficient of restitution prevails. Therefore, surfactants can be successfully used to obtain stable dispersions containing pigments.
[0015] However, if the electrochemical bilayer is damaged, for example by the addition of an electrolyte, the attractive force becomes dominant and the dispersion collapses. This situation can occur, for example, during the preparation of cosmetic formulations.
[0016] Furthermore, a further common problem associated with surfactants and other additives is that they can determine significant drawbacks in the properties of the formulation to which they are added. Rheological changes, such as a decrease in viscosity, are quite common. In addition, the use of surfactants has a significant impact on a wide range of essential properties of the formulation, including color intensity, opacity, coagulation, gloss, flooding, and floating.
[0017] Therefore, there is a great need to provide new technologies for producing stable formulations containing pigments, particularly in the fields of cosmetics and coatings. Such stable formulations containing pigments are expected to guarantee at least the following properties: i) minimal complexity of the manufacturing process, ii) good dispersibility, iii) good stability of the latter, and iv) strong coloration. [Prior art documents] [Non-patent literature]
[0018] [Non-Patent Document 1] Schudel et al., J. Colloid Interface Sci., 1997, 196, 241 [Overview of the project]
[0019] The present invention relates to a process for producing pigment composites comprising pigment particles having submicron size. Specifically, the main object of the present invention is a process for preparing a composite comprising submicron-sized particles of a metal oxide pigment and a natural-based organic compound, the process comprising the step of grinding the metal oxide pigment and the oligomer and / or polymer carbohydrate together in a ball mill to obtain a pigment composite comprising particles having a submicron particle size distribution and an outer surface covered with oligomers and / or polymer carbohydrates.
[0020] According to a preferred embodiment, the aforementioned pigment is a transition metal oxide pigment.
[0021] According to another form, the new pigment complex obtained by the aforementioned process is also an object of the present invention.
[0022] It has been experimentally observed that the aforementioned new pigment complex contains particles having a hydrodynamic diameter smaller than that of the same type of pigment particles not passing through the preparation process according to the present invention at neutral, slightly basic, and weakly basic pHs.
Brief Description of the Drawings
[0023] [Figure 1] It shows a skin preparation obtained by using a mixture of metal oxide pigment complexes according to the present invention. [Figure 2] It shows the pigment complexes obtained in Examples 1 to 3 below dispersed in water. [Figure 3] It shows the dispersion shown in Figure 2 when the supernatant is removed (remaining dispersion: left vial; supernatant: right vial). [Figure 4] It shows an example of a roll ball mill. [Figure 5] It shows an example of a cylindrical ball mill.
Modes for Carrying Out the Invention
[0024] According to the present invention, the term "pigment" means a colored, white, or black substance that can permanently impart its own color or hue to a dispersion material or substance and can impart a specific color to reflected light or transmitted light as a result of selective absorption of a specific wavelength, and the pigment usually has a high coloring power with respect to the material or substance to be mixed for coloring.
[0025] According to the present invention, the term "particle size distribution" means a numerical range including the minimum and maximum diameters of the particles forming the complex according to the present invention.
[0026] According to the present invention, the expression "submicron size" is intended to mean particles having a median diameter less than 1 μm.
[0027] As used herein, the term “ball mill” broadly refers to any milling apparatus that includes a grinding chamber (e.g., a jar) into which the material to be milled can be introduced, the grinding chamber including one or more freely moving balls, the movement of which causes the material to be milled to be ground, and as a general, non-limiting rule, the movement of the balls can be obtained by applying (one or more) rotational, swirling, and / or vibrating movements to the grinding chamber.
[0028] One preferred example of a ball mill is the "planetary ball mill," in which the grinding chamber can be set to rotate around its vertical axis, and optionally, complementary swirling motions around a suitable center of rotation can be further applied to the grinding chamber, and such (one or more) movements allow the grinding balls within the grinding chamber to move freely and mix with the material being ground, causing the grinding to occur. An example of a commercially available planetary ball mill is the Retsch PM 100.
[0029] Further examples of ball mills are the roll ball mill and the cylindrical ball mill. In both cases, the grinding chamber is set to rotate around its horizontal axis, and this movement allows the grinding balls within the chamber to move freely, mixing with the material being milled and causing it to grind. In a roll ball mill, the rotational motion is applied to the grinding chamber by contact between its outer surface and a counter-rotating rotating guide or roll (Figure 4). An example of a commercially available roll ball mill is the Tencan GQM-2-5. In a cylindrical ball mill, the rotational motion is applied to an element that extends from the horizontal axis of the grinding chamber or is indirectly fixed rotatably by a gear / V-belt (Figure 5). An example of a commercially available cylindrical ball mill is the Tencan QM-30L.
[0030] According to the present invention, the expression "ball-to-mass ratio" refers to the ratio between the total weight of balls / beads contained in the ball mill used during the grinding step b) described above and the total mass of the material to be ground, i.e., the metal oxide pigments and natural-based organic compounds supplied to the ball mill, or any other material ultimately supplied to the ball mill, supplied to the ball mill, for example, before or during the grinding step b).
[0031] According to the present invention, the term "storage life" refers to the length of time that the pigment complex obtained by the process of the present invention can be stored at room temperature without becoming unsuitable for use, that is, when properly dispersed in a medium, particularly an aqueous medium, a stable formulation with respect to phase separation and color can be obtained.
[0032] The present invention provides a process for preparing a complex containing submicron-sized particles of metal oxide pigments and natural-based organic compounds. a) A step of providing metal oxide pigments and oligomers and / or polymer carbohydrates, b) A step of grinding the metal oxide pigment and the oligomer and / or polymer carbohydrate in a ball mill to obtain a pigment composite comprising metal oxide particles having a submicron particle size distribution and an outer surface partially or completely covered with the oligomer and / or polymer carbohydrate, The mass ratio between the metal oxide pigment and the oligomer and / or polymer carbohydrate provided in step a) above is between 1:10 and 10:1.
[0033] Preferably, the grinding step b) described above is carried out under dry milling conditions.
[0034] According to a preferred embodiment, the mass ratio between the pigment and the oligomer and / or polymer carbohydrate is between 1:5 and 5:1.
[0035] As an advantage, as shown in the experimental section, increasing the mass ratio between the pigment and the oligomer and / or polymer carbohydrate can reduce the particle size distribution of the pigment composite obtained by the process according to the present invention.
[0036] Preferably, the grinding step b) described above is performed with ball-to-mass ratios that generally fall between 2:1 and 15:1. Ball-to-mass ratios particularly suitable for planetary ball mills are more selectively included between 3:1 and 10:1, and ball-to-mass ratios particularly suitable for roll ball mills or cylindrical ball mills are more selectively included between 2:1 and 7:1.
[0037] As an advantage, as shown in the experimental section, reducing the ball-to-mass ratio can also reduce the particle size distribution of the pigment composite obtained by the process according to the present invention.
[0038] Alternatively, the grinding step b) described above may be performed under wet milling conditions.
[0039] When the process of the present invention is carried out under wet milling conditions, a wetting material or lubricant may be added to the metal oxide pigment and oligomer and / or polymer carbohydrate before or during step b) above.
[0040] Preferably, the wetting material is water, ethyl alcohol, or a surfactant.
[0041] More preferably, the surfactant is selected from the group including esters of long-chain fatty acids, aryloxy alcohols, high molecular weight alcohols, alkyl ethers of glycerol, and equivalents thereof.
[0042] More preferably, the surfactant is added in an amount between 0.5% and 2.5% by weight of the total weight of the material supplied to the ball mill.
[0043] Generally speaking, the grinding step b) described above is preferably performed at a rotational speed between 200 rpm and 700 rpm, more preferably between 300 rpm and 550 rpm, for a time between 0.5 hours and 15 hours, more preferably between 1 hour and 9 hours, and these conditions are particularly suitable for planetary ball mills.
[0044] Alternatively, step b) above, which involves grinding, may be performed for a duration of 0.5 hours and 15 hours, more preferably 1 hour and 9 hours, at a rotational speed between 20 rpm and 400 rpm, more preferably between 20 rpm and 200 rpm, and these conditions are particularly suitable for roll ball mills or cylindrical ball mills.
[0045] In all the embodiments described above, preferred non-limiting examples of materials constituting the grinding balls are zirconia (i.e., zirconium oxide), stainless steel, etc. Preferred non-limiting examples of materials constituting the grinding chamber are zirconia, perfluorinated polymers, stainless steel, etc. Preferred non-limiting combinations of materials for the grinding balls and grinding chambers are alumina or zirconia balls in a ceramic chamber, zirconia balls in a zirconia chamber, zirconia balls in a polymeric perfluorinated chamber, and stainless steel balls in a stainless steel chamber. In addition to the examples described above, the constituent materials, as well as the dimensions of the grinding chamber and the dimensions / weight / quantity of the grinding balls, can be selected according to options conventionally applied in the art and, possibly, can be further adapted depending on the type and quantity of material to be milled.
[0046] An advantage of the present invention is that the process does not undergo particle re-aggregation during the milling process and makes it possible to obtain a pigment composite that is stable in terms of color during its storage life.
[0047] In particular, as will be shown in detail with reference to the experimental section, such pigment complexes can be easily and stably dispersed in liquid media, especially aqueous media, to obtain suspensions with good stability and strong coloration.
[0048] During the aforementioned grinding step b), the movement of the pigment particles is restricted, and the chemically preferred arrangement of interacting atoms is limited by the outer surface of the particles, which are formed such that the average size is reduced compared to the average size of the natural metal oxide pigment.
[0049] The newly formed surface can be immediately coated with (one or more) of the latter material to reduce re-aggregation, thanks to the co-grinding of oligomers and / or polymeric carbohydrate materials. In particular, hollow polymer structures of cyclodextrins, or fibrous or layered polysaccharides such as ionic and nonionic cellulose and cellulose derivatives, readily incorporate pigment particles.
[0050] Such covered aggregate particle complexes have a hydrophilic outer surface that plays a crucial role in the colloidal stability of the formulations in which they can be dispersed.
[0051] A further advantage is that during the grinding step b) described above, oxo complexes and / or hydrogen bond-stabilizing aggregates are formed between the aforementioned metal oxide pigment and the oligomer and / or polymer carbohydrate. Such oxo complexes or hydrogen bond-stabilizing aggregates prevent the formation of large particles under mechanochemical conditions, in other words, not only while the grinding step b) is being performed, but especially when the pigment complex thus obtained is dispersed in a suitable aqueous medium.
[0052] In particular, as will be shown in detail in the experimental section, the aforementioned pigment complex can be easily dispersed in aqueous media having a neutral to basic pH.
[0053] As a further improvement, the stable formulation thus formed has desirable settling properties that remain even after pH shifts or adjustments when dispersed in an aqueous medium.
[0054] A further improvement achieved by the process according to the present invention is the increased color stability of the pigment composites obtained in this manner, which depends on the particle size of the pigments. By limiting the self-aggregation of submicrometer and nanometer sized particles, the optical properties of their pigments are preserved, and their colors can remain unchanged for extended periods in both dispersed and non-dispersive forms.
[0055] Furthermore, as will be disclosed in more detail in the experimental section, a further improvement of the present invention is that the particles of the pigment composite obtained by the aforementioned process do not adhere to the surface of packaging materials such as glass and plastic, and do not cause unwanted discoloration of those materials.
[0056] According to the process of the present invention, the neutral-based organic compound, i.e., oligomers and / or polymeric carbohydrates, can be added to and mixed with the aforementioned metal oxide pigment at any stage of the process, preferably before or during step b) above.
[0057] Preferably, the metal oxide pigment is a transition metal oxide pigment.
[0058] More preferably, the metal oxide pigment can be selected from the group consisting of iron(III) oxide (CAS number: 1309-37-1 (red pigment) or CAS number: 51274-00-1 (yellow pigment)), iron(II) diferric oxide (CAS number: 1317-61-9, black pigment), titanium dioxide (CAS number: 13463-67-7), chromium(III) oxide (CAS number: 1308-38-9), manganese(IV) oxide (CAS number: 1313-13-9), zinc oxide (CAS number: 1314-13-2), cobalt(II) oxide (CAS number: 1307-96-6), zirconium(IV) oxide (CAS number: 1314-23-4), tungsten(VI) oxide (CAS number: 1314-35-8), and any combination thereof.
[0059] Preferably, the oligomer and / or polymer carbohydrate is selected from the group consisting of ionic cellulose, nonionic cellulose, derivatives of ionic or nonionic cellulose, starch, alginate, hyaluronic acid, chitosan, carrageenan, pectin, cyclodextrin, and any combination thereof.
[0060] In a more preferred embodiment, the oligomer and / or polymer carbohydrate is a cyclodextrin, more preferably a β-cyclodextrin.
[0061] Similarly, in a preferred embodiment, the oligomer and / or polymer carbohydrate is ionic cellulose, nonionic cellulose, or a cellulose derivative, more preferably carboxymethylcellulose or a salt thereof.
[0062] According to a preferred embodiment of the present invention, a base additive is added to the metal oxide pigment and the oligomer and / or polymer carbohydrate.
[0063] According to the process of the present invention, the base additive can be added to and mixed with the aforementioned metal oxide pigment at any stage of the process, preferably before or during step b) of the grinding process.
[0064] According to the Bronsted-Lowry acid-base theory, the above inorganic base additive can be an inorganic or organic base.
[0065] Similarly, in a preferred embodiment, the base additive may be an inorganic base additive, preferably selected from the group consisting of alkali hydroxides, alkaline earth hydroxides, carbonates, bicarbonates, and any combination thereof.
[0066] More preferably, the inorganic base additive is sodium hydroxide, sodium carbonate, or sodium bicarbonate.
[0067] Preferably, the mass ratio between the pigment and the inorganic base additive is between 1:2 and 10:1.
[0068] More preferably, the mass ratio between the pigment and the inorganic base additive is between 1:2 and 5:1.
[0069] According to a preferred embodiment of the present invention, the base additive is an organic base additive, and preferably the organic base additive is selected from amino acids, alkyl or arylalkylamines, hydroxyalkyl or (hydroxy)arylalkylamines, hydroxyalkyl or (hydroxy)arylalkylureas, hydroxyalkyl or (hydroxy)arylalkylthioureas, or any combination thereof.
[0070] The above amino acids may be L-amino acids, D-amino acids, or mixtures thereof.
[0071] Preferably, the organic base additive is arginine, tris(hydroxymethyl)methylamine, or urea.
[0072] In a more preferred embodiment, the base additive is a combination of an inorganic base and an organic base, preferably a combination of one of the aforementioned inorganic base additives and one of the aforementioned organic base additives.
[0073] An advantage is that when a base additive is added to the metal oxide pigment and the oligomer and / or polymer carbohydrate, the ability of the aforementioned pigment complex to form a stable formulation in a moderately basic pH state and in a state after a pH shift or adjustment can be improved.
[0074] More specifically, it has been found that, surprisingly, when the above-mentioned base additives are added, several classes of oligomers and / or polymeric carbohydrates can adhere more favorably to the pigment particles during formation during the aforementioned grinding step b).
[0075] For example, as shown in the experimental section below, when natural metal oxide pigments are ground together with cyclodextrin and a base additive, the resulting pigment complex can be dispersed more effectively in an aqueous-based dispersion compared to a similar pigment complex produced without the addition of a base additive.
[0076] Without being bound by scientific theory, when natural metal oxide pigments are ground together with cyclodextrin and base additives, the base additives deprotonate some of the hydroxyl groups of the cyclodextrin, creating strong intermolecular interactions with the surface of the pigment particles being formed, thereby enhancing the capabilities of the cyclodextrin, as described later.
[0077] According to a preferred embodiment of this process, during step a) above, which provides the metal oxide pigment and the oligomer and / or polymer carbohydrate, the oligomer and / or polymer carbohydrate provided is β-cyclodextrin, and at the same time, the inorganic base additive added to the metal oxide pigment and the β-cyclodextrin is NaOH.
[0078] According to another preferred embodiment of the process, during step a) above, which provides the metal oxide pigment and the oligomer and / or polymer carbohydrate, the oligomer and / or polymer carbohydrate provided is β-cyclodextrin, and at the same time, the inorganic base additive added to the metal oxide pigment and the β-cyclodextrin is NaHCO3.
[0079] According to another preferred embodiment of the process, during step a) above, which provides the metal oxide pigment and the oligomer and / or polymer carbohydrate, the oligomer and / or polymer carbohydrate provided is β-cyclodextrin, and at the same time, the organic base additive added to the metal oxide pigment and the β-cyclodextrin is arginine.
[0080] According to another preferred embodiment of the process, during step a) above, which provides a metal oxide pigment and an oligomer and / or polymer carbohydrate, the oligomer and / or polymer carbohydrate provided is β-cyclodextrin, and at the same time, the organic base additive added to the metal oxide pigment and the β-cyclodextrin is tris(hydroxymethyl)methylamine.
[0081] According to another preferred embodiment of the process, during step a) above, which provides the metal oxide pigment and the oligomer and / or polymer carbohydrate, the oligomer and / or polymer carbohydrate provided is β-cyclodextrin, and at the same time, the organic base additive added to the metal oxide pigment and the β-cyclodextrin is urea.
[0082] According to this embodiment of the process, the auxiliary material can be ground together with the metal oxide pigment and the oligomer and / or polymer carbohydrate during the grinding step b) described above.
[0083] According to the process of the present invention, the auxiliary material can be added to and mixed with the aforementioned natural metal oxide pigment at any stage of the process, preferably before or during step b) of the grinding process.
[0084] More preferably, the auxiliary material can be selected from the group comprising disinfectants, stabilizers or fillers, or hydrophilic active additives, such as urea or other organic or inorganic salts.
[0085] In another embodiment, the present invention also relates to a pigment composite obtained by the aforementioned process.
[0086] As shown in the following experimental section, the pigment composite according to the present invention comprises pigment particles having a submicron particle size distribution and an outer surface partially or completely covered with the oligomer and / or polymer carbohydrates.
[0087] More specifically, when the particles of the composite of the present invention are dispersed in an aqueous medium, they have an average hydrodynamic diameter of less than 1 μm, preferably between 50 nm and 800 nm, more preferably between 100 nm and 500 nm, as measured by dynamic light scattering (also known as photon correlation spectroscopy or quasi-elastic light scattering) according to procedure ISO 22412:2017.
[0088] According to the present invention, particle size and their distribution are appropriately characterized by the hydrodynamic diameter of the particles measured by photon correlation spectroscopy, also known as dynamic light scattering (DLS) (Chu, B. Laser light scattering: Basic Principles and Practice. Academic Press., 1992; Berne, BJ; Pecora, R. Dynamic Light Scattering. Courier Dover Publications, 2000). The effective hydrodynamic diameter of the particles is calculated by multimodal analysis of the measured autocorrelation function of the scattered light, as taught by Frisken B. et al. (J. Applied Optics, 2001, 40, 4087-4091).
[0089] According to a preferred embodiment, the aforementioned pigment complex can be stably suspended in an aqueous medium, the aqueous medium having a pH preferably between 6 and 12, more preferably between 6 and 9.
[0090] More preferably, the pigment composite according to the present invention has a shelf life contained between 6 months and 48 months.
[0091] As has already been described regarding this process and will be shown in detail in the experimental section, the pigment composite of the present invention does not undergo particle reaggregation during the milling process and is absolutely stable with respect to its color throughout its storage life.
[0092] In particular, as will be shown in detail with reference to the experimental section, such pigment complexes can be easily and stably dispersed in liquid media, especially aqueous media, to obtain suspensions with good stability and strong coloration.
[0093] If the grinding step b) described above is performed under dry milling conditions, the pigment composite is in a dry form. If the grinding step b) described above is performed under wet milling conditions, the pigment composite of the present invention may be in the form of a viscous paste, for example, an aqueous paste.
[0094] Consistently, in another form, the present invention also relates to the use of the aforementioned pigment complex for coloring cosmetic, paint, coating formulations, or other applications where a smooth, uniformly covered and colored surface is required.
[0095] The use of the aforementioned pigment complex in cosmetics is particularly preferred.
[0096] According to a preferred embodiment, the pigment complex of the present invention can be effectively used for the preparation of cosmetic compositions, more preferably for coloring cosmetic compositions such as foundations, primers, concealers, lipsticks, lip glosses, bronzers, eyeshadows, eyeliners, eyebrow pencils, mascaras, enamels, or any other cosmetic compositions containing pigments. This embodiment extends to a method for preparing, particularly for coloring, cosmetic compositions such as foundations, primers, concealers, lipsticks, lip glosses, bronzers, eyeshadows, eyeliners, eyebrow pencils, mascaras, enamels, or any other cosmetic compositions, the method comprising the step of adding the pigment complex of the present invention to each of these cosmetic compositions.
[0097] Therefore, referring to another form, the present invention relates to a cosmetic composition comprising the aforementioned pigment complex, wherein the cosmetic composition is preferably a product for facial cosmetic use.
[0098] Alternatively, the aforementioned pigment complexes can be used as coloring additives in cement, gypsum plaster, soap, paper, aqueous and non-aqueous printing inks, such as inks for gravure printing, screen printing or paper printing, and preparations for coloring leather by rubber grids or coatings. This embodiment extends to a method for coloring materials such as cement, gypsum plaster, soap, paper, and aqueous and non-aqueous printing inks, the method comprising the step of adding the pigment complex of the present invention to each of these compositions.
[0099] The present invention is described below in no particular way by the following embodiments.
[0100] experiment Example 1: Preparation of pigment complex under neutral conditions β-cyclodextrin was added to natural metal oxides according to a metal oxide / carbohydrate mass ratio of 1:2. Red iron oxide supplied by SunChemical Co. was used.
[0101] β-cyclodextrin and natural metal oxide were mixed together and milled in a planetary ball mill (Retsch PM 100) at 500 rpm according to a ball-to-mass ratio of 12:1. The milling process was carried out for 90 minutes.
[0102] A red fine powder was obtained.
[0103] The procedure was repeated using carboxymethylcellulose (CMC) instead of β-cyclodextrin (β-CD). The metal oxide / carbohydrate ratio was kept constant at 1:2, and the milling process was carried out under the same conditions.
[0104] A red fine powder was obtained.
[0105] Subsequently, both the β-cyclodextrin and carboxymethylcellulose procedures were repeated for three other natural pigments under the same milling conditions and with the same metal oxide / carbohydrate ratio. The natural pigments used were: yellow iron oxide, white titanium oxide, and green chromium oxide (all metal oxides supplied by Sun Chemical).
[0106] The total number of experiments conducted under neutral conditions was eight.
[0107] Example 2: Preparation of pigment complex under slightly basic conditions β-cyclodextrin was added to natural metal oxides according to a metal oxide / carbohydrate ratio of 1:2. Red iron oxide supplied by Sun Chemical was used.
[0108] β-cyclodextrin and natural metal oxides were mixed together, and sodium bicarbonate was added to them. The mass ratios of the metal oxide, β-cyclodextrin, and sodium bicarbonate were 1:2:1, respectively.
[0109] The mixture thus obtained was added to a planetary ball mill (Retsch PM 100) and then milled at 500 rpm according to a ball-to-mass ratio of 12:1. This milling process was carried out for 90 minutes.
[0110] A red fine powder was obtained.
[0111] The procedure was repeated for three other natural pigments under the same milling conditions and with the same metal oxide / carbohydrate / NaHCO3 ratios, and the natural pigments used were: yellow iron oxide, white titanium oxide, and green chromium oxide.
[0112] The total number of experiments conducted under slightly basic conditions was four.
[0113] Example 3: Preparation of pigment composites under basic conditions β-cyclodextrin was added to natural metal oxides according to a metal oxide / carbohydrate mass ratio of 1:2. Red iron oxide supplied by Sun Chemical was used.
[0114] β-cyclodextrin and natural metal oxides were mixed together, and sodium hydroxide was added to them. The mass ratios of the metal oxide, β-cyclodextrin, and sodium hydroxide were 2:4:1, respectively.
[0115] The mixture thus obtained was added to a planetary ball mill (Retsch PM 100) and then milled at 500 rpm using a ball-to-mass ratio of 12:1. This milling process was carried out for 90 minutes.
[0116] A red fine powder was obtained.
[0117] The procedure was repeated for three other natural pigments under the same milling conditions, using the same ratio of metal oxide / carbohydrate / NaOH. The natural pigments used were: yellow iron oxide, white titanium oxide, and green chromium oxide.
[0118] The total number of experiments conducted under basic conditions was four.
[0119] Example 4: Milling of natural pigments under neutral conditions (comparative example) The procedure of Example 1 was carried out under the same milling conditions using only natural red iron oxide. A pigment milled into a red powder form was obtained.
[0120] The powder obtained in this manner showed a slightly darker color compared to the pigment composite obtained in Example 1 according to the present invention.
[0121] The aforementioned procedure was also performed on natural yellow iron oxide, natural white titanium oxide, and green chromium oxide.
[0122] Example 5: Determination of hydrodynamic diameter in a neutral suspension To evaluate the particle size and its distribution, the pigment composite obtained in Example 1 was appropriately characterized by photon correlation spectroscopy.
[0123] 1–5 mg of each sample prepared in Example 1 was suspended in 4 ml of distilled water in a clear plastic cuvette (90° scattering of 678 nm laser light), and the light scattering was measured using a Brookhaven 90Plus Particle Size Analyzer instrument according to procedure ISO 22412:2017.
[0124] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments (data acquisition period: 30 seconds per run).
[0125] Table 1 shows the calculated distribution of the hydrodynamic diameter (nanometers) of the pigment composite in a neutral suspension (pH=6~7).
[0126] The pigment powder obtained in Example 4 was also appropriately characterized by photon correlation spectroscopy.
[0127] Table 1 shows the calculated hydrodynamic diameter distribution of the milled pigment powders obtained in Examples 1 and 4 in a neutral suspension (pH=6~7).
[0128] [Table 1]
[0129] With respect to red iron oxide particles, it is evident that the composites obtained by the process according to the present invention generally have smaller hydrodynamic diameters. The distribution of hydrodynamic diameters is shifted considerably to 150-200 nm for both red iron oxide milled with β-CD (40% of the total number of pigment particles) and red iron oxide milled with CMC (38% of the total number of pigment particles) when compared to the distribution of hydrodynamic diameters of iron oxide milled without the use of oligomers and / or polymer carbohydrates.
[0130] Remarkable improvements were also achieved with white titanium oxide and green chromium oxide. Compared to pigments milled without additives under the same conditions, white titanium oxide milled with β-CD, white titanium oxide milled with CMC, and green chromium oxide milled with CMC each showed a reduction in hydrodynamic diameter.
[0131] It can be observed that some of the composites according to the present invention, produced by milling natural pigments together with CMC, have an even smaller diameter than the composites obtained by milling the same pigments with β-CD.
[0132] Example 6: Determination of hydrodynamic diameter in a slightly basic suspension To evaluate the particle size and its distribution, the pigment composite obtained in Example 2 was appropriately characterized by photon correlation spectroscopy.
[0133] 1 to 5 mg of each sample prepared in Example 2 was suspended in 4 ml of distilled water, and the same measurement as in Example 5 was performed.
[0134] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments.
[0135] Table 2 shows the calculated distribution of the hydrodynamic diameter (nanometers) of the pigment composite in a slightly basic suspension (pH = 7.5 to 8.5).
[0136] [Table 2]
[0137] When comparing Table 1 and Table 2 together, it is clear that particles obtained by milling pigments with β-CD in combination with NaHCO3 generally have a hydrodynamic diameter smaller than that of particles obtained by milling pigments with β-CD without inorganic additives and dispersed in a neutral environment.
[0138] Example 7: Milling of natural pigments under neutral conditions (comparative example) The procedure of Example 3 was carried out under the same milling conditions using only natural red iron oxide and NaOH, without oligomers and / or polymeric carbohydrates. Milled pigment was obtained in the form of red powder.
[0139] The powder obtained in this manner showed a slightly darker color compared to the pigment composite obtained in Example 3 according to the present invention.
[0140] The aforementioned procedure was also performed on natural yellow iron oxide, natural white titanium oxide, and green chromium oxide.
[0141] Example 8: Determination of hydrodynamic diameter in a basic suspension To evaluate the particle size and its distribution, the pigment composites obtained in Example 3 were appropriately characterized by photon correlation spectroscopy.
[0142] 1 to 5 mg of each sample prepared in Example 3 was suspended in 4 ml of distilled water, and measurements were performed as in Example 5.
[0143] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments.
[0144] Table 3 shows the calculated distribution of the hydrodynamic diameter of the pigment complex in a weakly basic suspension (pH=10-11).
[0145] To evaluate the particle size and its distribution, the pigment powder prepared in Example 7 was also appropriately characterized by photon correlation spectroscopy.
[0146] Table 3 shows the calculated hydrodynamic diameter distribution of the milled pigment powders obtained in Examples 3 and 7 in a weakly basic suspension (pH = 10-11).
[0147] [Table 3]
[0148] When viewing Tables 1, 2, and 3 together, it is clear that the particles obtained by milling the pigment with β-CD in combination with NaOH generally have a smaller hydrodynamic diameter than those obtained by milling the pigment with β-CD without inorganic additives, and not only in terms of the diameter of the particles dispersed in a neutral environment, but also, surprisingly, smaller than the diameter of the particles obtained by milling the pigment with β-CD in combination with NaHCO3.
[0149] In particular, milling red iron oxide or green chromium oxide together with β-CD and NaOH resulted in a significant improvement over composites obtained by milling pigments together with β-CD and NaHCO3 (less than 2% of particles obtained by milling red iron oxide, β-CD, and NaHCO3 had a hydrodynamic diameter of less than 150 nm, compared to approximately 58% of particles obtained by milling red iron oxide, β-CD, and NaOH).
[0150] For comparison, the particle size of pigments milled by a process not according to the present invention (Example 7) was also measured and is shown in Table 3.
[0151] As is clear from Table 3, the particles obtained by milling the pigment together with β-CD and NaOH generally have a smaller hydrodynamic diameter compared to the particles obtained by the procedure of Example 7.
[0152] Example 9: Preparation of pigment composites and determination of hydrodynamic diameter under basic conditions with increased metal oxide content. β-cyclodextrin was added to natural metal oxides according to a metal oxide / carbohydrate mass ratio of 2:1.
[0153] β-cyclodextrin and natural white titanium were mixed together. NaHCO3 was added before milling.
[0154] The mass ratios of metal oxide, β-cyclodextrin, and sodium bicarbonate were 4:2:1, respectively.
[0155] The mixture thus obtained was milled in a planetary ball mill (Retsch PM 100) at 550 rpm and using a ball-to-mass ratio of 9:1. The milling process was carried out for 150 minutes.
[0156] This procedure was repeated under the same conditions by adding NaOH instead of NaHCO3.
[0157] To evaluate the particle size and its distribution, the resulting pigment composites were appropriately characterized by photon correlation spectroscopy.
[0158] 1 to 5 mg of each sample prepared in this way was suspended in 4 ml of distilled water, and measurements were performed as in Example 5.
[0159] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments.
[0160] Table 4 shows the calculated hydrodynamic diameter distributions of the composites thus obtained in slightly basic and weakly basic suspensions, respectively.
[0161] [Table 4]
[0162] Surprisingly, by comparing the particle size distribution shown in Table 4 with the particle size distributions of the white titanium oxide composite (white titanium oxide, β-CD and NaHCO3) in Table 2 and the white titanium oxide (white titanium oxide, β-CD and NaOH) in Table 3, a significant reduction in hydrodynamic diameter is achieved when the amount of metal oxide is increased relative to both the amount of β-CD and the inorganic additive.
[0163] Example 10: Preparation of pigment composites and determination of hydrodynamic diameter under basic conditions with reduced ball-to-mass ratio. Carboxymethylcellulose was added to natural yellow iron oxide according to a metal oxide / carbohydrate mass ratio of 1:2.
[0164] Carboxymethylcellulose and natural yellow iron oxide were mixed together.
[0165] The mixture thus obtained was milled in a planetary ball mill (Retsch PM 100) at 450 rpm and using a ball-to-mass ratio of 3:1. The milling process was carried out for 180 minutes.
[0166] To evaluate the particle size and its distribution, the resulting pigment composites were appropriately characterized by photon correlation spectroscopy.
[0167] 1 to 5 mg of the sample prepared in this way was suspended in 4 ml of distilled water, and measurements were performed as in Example 5.
[0168] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments. pH was measured using a glass electrode.
[0169] Table 5 shows the calculated hydrodynamic diameter distributions of the composites thus obtained in a neutral suspension.
[0170] [Table 5]
[0171] When comparing Table 1 and Table 5, it is clear that the composite obtained by milling yellow iron oxide with CMC at a ball-to-mass ratio of 10 has particles with a larger average hydrodynamic diameter compared to the particles of the composite obtained by milling the same pigment with CMC at a ball-to-mass ratio of 6.
[0172] In particular, the composite obtained by milling yellow iron oxide together with CMC at a ball-to-mass ratio of 10 contained approximately 41% of particles with a hydrodynamic diameter of less than 250 nm, while more than 77% of the particles of the yellow iron oxide composite in Table 5 had a hydrodynamic diameter of less than 250 nm.
[0173] Example 11: Evaluation of the striping effect in a skin cosmetic liquid composition for facial makeup. First, gels were prepared at 75°C using disodium EDTA (0.20 g), carbomer (0.80 g), water (90 ml), yellow iron oxide (0.80 g) milled with CMC as prepared in Example 1, titanium dioxide (4.10 g) milled with β-CD and NaOH as prepared in Example 3, and red iron oxide (0.10 g) milled with β-CD and NaOH as prepared in Example 3.
[0174] An emulsion was prepared by adding the thus obtained Pemulen TR-1 (0.15 g) and ethylhexyl palmitate (3.00 g) to the gel using an industrial mixer. After 60 minutes, the resulting emulsion was subsequently cooled. After cooling, Euxil PE9010 (0.90 g) was added as a preservative. Finally, the emulsion was homogenized.
[0175] A homogeneity test was performed on the obtained neutral emulsion (pH 6-8) using the following method: small droplets of the emulsion were placed between two glass plates, and then slid over each other. The thin emulsion layer that separated from each other and remained on one of the glass plates was analyzed.
[0176] As shown in Figure 1, the cosmetic emulsion obtained by using the pigment complex mixture according to the present invention is homogeneous and very gentle on the eyes.
[0177] In fact, the above pigment complex was easily and stably dispersed in an aqueous medium, after which a stable emulsion was obtained. The emulsion had a strong color hue and completely removed unwanted stripes.
[0178] Example 12: Sedimentation test of prepared solid pigments The sedimentation properties of the following pigment complexes obtained in Examples 1-3 were evaluated: red iron oxide milled with CMC dispersed in water at pH 6-7 (Reference 1); red iron oxide milled with β-CD and NaHCO3 dispersed in water at pH 7.5-8.5 (Reference 2); and red iron oxide milled with β-CD and NaOH dispersed in water at pH 11 (Reference 3).
[0179] In parallel, the sedimentation characteristics of the following pigment obtained in Example 4, which does not conform to the present invention, were evaluated: red iron oxide dispersed in water with a pH of 6-7 and milled (Reference 4).
[0180] The aforementioned pigment complex and pigment samples from Example 4 were weighed out at approximately 5 mg each into 5 ml glass vials. 4 ml of water was added to each vial, and then the glass vials were closed and shaken for 30 seconds at room temperature in a parallel experimental shaker at 120 rpm.
[0181] The photograph shown in Figure 2 was taken 18 hours later, and the resulting dispersion is still in the same state at room temperature.
[0182] Figure 3 shows the aforementioned dispersion after a certain amount of liquid has been taken out from each glass vial (the vial on the left) and placed into another vial (the vial on the right).
[0183] As is clear from Figure 3, the pigment composite according to the present invention did not adhere to the wall of the aforementioned glass vial.
[0184] In contrast, when a certain amount of the dispersion of Reference 3 was taken out of its glass vial, it was clear that pigments not in accordance with the present invention adhered to the glass wall of the container.
[0185] Therefore, it has been demonstrated that the pigment composite according to the present invention does not adhere to glass, thus avoiding results that are completely undesirable for consumers, especially consumers of cosmetics, and have been particularly met with disapproval.
[0186] Example 13: Preparation of pigment composites under neutral conditions in a roll ball mill β-cyclodextrin and carboxymethylcellulose were added to natural metal oxides according to a metal oxide / carbohydrate mass ratio of 7:3. Red iron oxide supplied by Sun Chemical was used.
[0187] β-cyclodextrin, carboxymethylcellulose, and natural metal oxide were mixed together and milled in a ceramic jar of a roll ball mill (Tencan GQM-2-5) at nominally 200 rpm using zirconia balls according to a ball-to-mass ratio of 4.5:1. The milling process was carried out for 4 hours.
[0188] A red fine powder was obtained.
[0189] Subsequently, both the β-cyclodextrin and carboxymethylcellulose procedures were repeated for three other natural pigments under the same milling conditions and with the same metal oxide / carbohydrate ratio. The natural pigments used were: yellow iron oxide, black iron oxide, and white titanium oxide (all metal oxides supplied by Sun Chemical).
[0190] The total number of experiments conducted under neutral conditions was four.
[0191] Example 14: Preparation of pigment composites under neutral conditions in a roll ball mill using different milling materials The procedure of Example 13, using β-cyclodextrin and carboxymethylcellulose, was repeated for four different types of natural pigments under the same milling conditions and with the same metal oxide / carbohydrate ratio. The natural pigments used were: yellow iron oxide, red iron oxide, black iron oxide, and white titanium oxide (all metal oxides were supplied by Sun Chemical).
[0192] The total number of experiments conducted under neutral conditions was four.
[0193] Subsequently, the procedure using both β-cyclodextrin and carboxymethylcellulose was repeated using four other different types of milling media: zirconia balls in a zirconia jar, zirconia balls in a polymer perfluorinated jar, and stainless steel balls in a stainless steel jar.
[0194] The total number of experiments conducted under neutral conditions was 12.
[0195] Example 15: Determination of hydrodynamic diameter in a neutral suspension To evaluate the particle size and its distribution, the pigment composites obtained in Example 13 were appropriately characterized by photon correlation spectroscopy.
[0196] 1–5 mg of each sample prepared in Example 13 was suspended in 4 ml of distilled water in a clear plastic cuvette (90° scattering of 675 nm laser light), and the light scattering was measured using a Brookhaven 90Plus Particle Size Analyzer instrument according to ISO 22412:2017.
[0197] The sample was shaken again, and the particle size was calculated using a multimodal intensity distribution model by a weighted average of nine consecutive experiments (data acquisition period: 30 seconds per run).
[0198] Table 1 shows the calculated distribution of the hydrodynamic diameter (nanometers) of the pigment composite in a neutral suspension (pH=6~7).
[0199] Table 6 shows the calculated hydrodynamic diameter distribution of the milled pigment powder obtained in Example 13 under neutral conditions (pH=6~7).
[0200] [Table 6]
[0201] With respect to red iron oxide particles, it is clear that the composites obtained by the process according to the present invention generally have different hydrodynamic diameter distributions. The hydrodynamic diameter distribution is shifted considerably to lower nm in all cases when compared to the hydrodynamic diameter distribution of iron oxide milled without the use of oligomers and / or polymer carbohydrates. Different milling media did not exhibit inherently different hydrodynamic radius distributions.
Claims
1. A process for the preparation of a composite comprising particles of a metal oxide pigment and a natural-based organic compound having a median diameter of less than 1 μm, comprising: a) providing a metal oxide pigment and an oligomeric and / or polymeric carbohydrate; b) grinding said metal oxide pigment and said oligomeric and / or polymeric carbohydrate in a ball mill to obtain a pigment composite comprising metal oxide particles having a median size of less than 1 μm and an outer surface partially or completely covered by said oligomeric and / or polymeric carbohydrate, the mass ratio between the metal oxide pigment and the oligomeric and / or polymeric carbohydrate provided in step a) is comprised between 1:10 and 10:1; and A process wherein a base additive is added and mixed with the metal oxide pigment before or during the grinding step b), wherein the base additive comprises an inorganic base additive selected from the group consisting of alkali hydroxides, alkaline earth hydroxides, carbonates, bicarbonates, and any combination thereof.
2. 2. The process according to claim 1, wherein the mass ratio between said metal oxide pigment and said oligomeric and / or polymeric carbohydrate is comprised between 1:5 and 5:
1.
3. 3. The process of claim 1 or 2, wherein the ball mill is selected from the group consisting of a planetary ball mill, a roll ball mill, and a cylindrical ball mill.
4. The process according to any one of claims 1 to 3, wherein the grinding step b) is carried out with a ball to mass ratio comprised between 2:1 and 15:
1.
5. The process of claim 4, wherein the grinding step b) is carried out with a ball-to-mass ratio comprised between 2:1 and 7:
1.
6. The process according to any one of claims 1 to 5, wherein the grinding step b) is carried out under dry milling conditions or under wet milling conditions.
7. The process according to any one of claims 1 to 6, wherein the grinding step b) is carried out at a rotation speed of between 200 rpm and 700 rpm.
8. The process of claim 7, wherein the grinding step b) is carried out at a rotational speed of between 300 rpm and 550 rpm.
9. The process according to any one of claims 1 to 8, wherein the grinding step b) is carried out for a time between 0.5 hours and 15 hours.
10. The process of claim 9, wherein the grinding step b) is carried out for a time period between 1 hour and 9 hours.
11. The process of any one of claims 1 to 10, wherein the metal oxide pigment is a transition metal oxide pigment.
12. The process of claim 11, wherein the transition metal oxide pigment is selected from the group consisting of iron (III) oxide, ferric (III) oxide, iron (II) oxide, titanium oxide, chromium (III) oxide, manganese (IV) oxide, zinc oxide, cobalt (II) oxide, zirconium (IV) oxide, tungsten (VI) oxide, and any combination thereof.
13. 13. The process according to any one of claims 1 to 12, wherein the oligomeric and / or polymeric carbohydrate is selected from the group consisting of ionic cellulose, non-ionic cellulose, ionic or non-ionic derivatives of cellulose, starch, alginate, hyaluronate, chitosan, carrageenan, pectin, cyclodextrin, and any combination thereof.
14. 14. The process of claim 13, wherein the oligomeric and / or polymeric carbohydrate is a cyclodextrin.
15. The process of claim 14, wherein the oligomeric and / or polymeric carbohydrate is β-cyclodextrin.
16. 14. The process of claim 13, wherein the oligomeric and / or polymeric carbohydrate is an ionizable cellulose, a non-ionizable cellulose or a cellulose derivative.
17. The process of claim 16, wherein the oligomeric and / or polymeric carbohydrate is carboxymethylcellulose or a salt thereof.
18. The process of any one of claims 1 to 17, wherein the inorganic base additive is sodium hydroxide, sodium carbonate or sodium bicarbonate.
19. 20. The process of claim 18, wherein the weight ratio between the metal oxide pigment and the inorganic base additive is comprised between 1:2 and 10:
1.
20. The process of claim 19, wherein the mass ratio between the metal oxide pigment and the inorganic base additive is between 1:2 and 5:
1.
21. 2. The process of claim 1, wherein the base additive further comprises an organic base additive selected from an amino acid, an alkyl or arylalkyl amine, a hydroxyalkyl or (hydroxy)arylalkyl amine, a hydroxyalkyl or (hydroxy)arylalkyl urea, a hydroxyalkyl or (hydroxy)arylalkyl thiourea, or any combination thereof.
22. A pigment complex comprising a metal oxide pigment, an oligomeric and / or polymeric carbohydrate, and an inorganic base additive selected from the group consisting of alkali hydroxides, alkaline earth hydroxides, carbonates, bicarbonates, and any combination thereof, wherein said pigment complex is comprised of particles having an average hydrodynamic diameter of less than 1 μm when measured according to procedure ISO 22412:2017, said particles having an outer surface in which the metal oxide pigment is partially or completely covered by the oligomeric and / or polymeric carbohydrate.
23. The pigment complex of claim 22, wherein the particles have an average hydrodynamic diameter between 100 nm and 800 nm when measured according to procedure ISO 22412:2017.
24. The pigment complex of claim 23, wherein the particles have an average hydrodynamic diameter between 100 nm and 500 nm when measured according to procedure ISO 22412:2017.
25. 25. The pigment complex according to any one of claims 22 to 24, which is stably suspended in an aqueous medium, said aqueous medium having a pH comprised between 6 and 12.
26. The pigment complex of claim 25, wherein the aqueous medium has a pH comprised between 6 and 9.
27. A cosmetic composition comprising the pigment complex according to any one of claims 22 to 26.
28. The cosmetic composition of claim 27, which is a facial cosmetic product.
29. Use of a pigment complex described in any one of claims 22 to 26 in a cosmetic for the preparation of a cosmetic composition.